Technostress and Fintech Usage Intention: Exploring Gen Z's Experience with P2P Services in Indonesia - Putinagari, Meutia Wanni; Saputra, Muhardi; Nurtrisha, Widyatasya Agustika; Febriyani, Widia (International Conference on Bio-engineering for Smart Technologies (Online), 2025)
This study presents a comprehensive model that utilizes technostress factors to measure the behavioral intention of Gen Z in Indonesia towards the fintech application X Paylater. The relationship between key adoption factors is investigated using Partial Least Squares Structural Equation Modeling (PLS-SEM). To improve the accuracy of the model, low-loading indicators (outer loading < 0.70) are removed, which increases reliability and validity. The findings indicate that subjective norms (β = 0.499) and perceived behavioral control (β = 0.280) have a significant impact on behavioral intention, while security concerns (β = −0.059) serve as a barrier to adoption. The model shows strong predictive ability, with behavioral intention showing the highest explanatory power (R 2 = 0.440).